The Effect of Applying Multilevel Directed Strategy Based on Nerolinguistic Programing (NLP) on Improving Digital Achievement for High Jump Effectiveness and Self-Esteem among Students of the College of Sports Sciences at the University of Jordan (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
The study aimed to identify the effect of a multi-level directed strategy based on neurolinguistic programing (NLP) on improving the digital achievement of high jump effectiveness and self-esteem among students of the College of Sports Sciences at the University of Jordan, in particular among students enrolled in the Athletics Course (2) in the academic year 2020/2021. To achieve this goal, the researcher  used The experimental approach on a sample consisting of (34) students from the course of Athletics (2), who were distributed in two groups: an experimental group and a control group, with (17) students in each group. The educational program was applied using a multi-level strategy directed based on NLP on the students of the experimental group studying the effectiveness of the high jump in the summer semester, with (16) educational units, while the control group was subjected to the traditional method. To collect the study data, a tool was designed to measure the self-esteem skills of the course of Athletics (2) students and digital achievement in accordance with the International Law of Athletics. The researchers used the statistical methods of Arithmetic means, standard deviations, Pearson correlation coefficient, independent sampling t-test and and T test for cross-linked samples. The results of the study showed that there are statistically significant differences between the two groups in the numerical achievement of the effectiveness of the high jump and self-esteem among the students of the course of Athletics (2) in favor of the experimental group with higher arithmetic averages compared to the averages of the control group.The researcher recommends that students should be given the opportunity to use a multi-level directed strategy based on NLP and conduct similar studies on the impact of this strategy on teaching team and individual games with stages and technical characteristics that differ from athletics courses.
Keywords: Strategy; Multilevel; Neurolinguistic Programing (NLP); Athletics; High Jump; Self-Ssteem